Alternating Hemiplegia of Childhood: Genotype–Phenotype Correlations in a Cohort of 39 Italian Patients - Cordani, Ramona; Stagnaro, Michela; Pisciotta, Livia; Tiziano, Francesco Danilo; Calevo, Maria Grazia; Nobili, Lino; , I.B.AHC Consortium; De Grandis, Elisa (Frontiers in Neurology, 2021)
Alternating Hemiplegia of Childhood is a rare neurological disease characterized by paroxysmal movement disorders and chronic neurological disturbances, with onset before 18 months of age. Mutations in the ATP1A3 gene have been identified in up to 80% of patients. Thirty-nine patients (20 females, 19 males, mean age 25.32 years [7.52-49.34]) have been recruited through the Italian Biobank and Clinical Registry for Alternating Hemiplegia of Childhood. Demographic data, genotype, paroxysmal movement disorders, chronic neurological features and response to flunarizine have been analyzed. ATP1A3 gene mutations have been detected in 92.3% of patients. Patients have been divided into three groups: p.Asp801Asn mutation patients (26%), p.Glu815Lys cases (23%), and patients with other ATP1A3 mutations , and statistically compared. The Italian cohort has a higher percentage of ATP1A3 gene mutation than reported in literature (92.3%). Our data confirm a more severe phenotype in patients with p.Glu815Lys mutation, with an earlier age of onset of plegic (p. 0.02 in the correlation with other mutations) and tonic attacks. P.Glu815Lys patients most frequently present altered muscle tone, inability to walk (p. 0.01 comparing p.Glu815Lys and p.Asp801Asn mutations), epilepsy, and a more severe grade of dystonia (p. < 0.05 comparing p.Glu815Lys and p.Asp801Asn mutations). They have moderate/severe intellectual disability and severe language impairment (p.<0.05). Interestingly, flunarizine seems to be more efficacious in patients with p.Glu815Lys mutation than p.Asp801Asn. In conclusion, our research suggests a genotype-phenotype correlation and provides information on this disorder's features, clinical course, and treatment.